2013
DOI: 10.1093/infdis/jit252
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Herpes Simplex Virus Type 2 After Initiation of Antiretroviral Therapy

Abstract: The prevalence of HSV-2 shedding and GUD increased significantly after ART initiation, possibly because of immune reconstitution inflammatory syndrome. Acyclovir significantly reduced both GUD and HSV-2 shedding and should be considered to mitigate these effects following ART initiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 34 publications
6
48
2
1
Order By: Relevance
“…The pathogenetic mechanisms that trigger the HHV-6 and HHV-7 reactivation in PR are still poorly understood [31]. Although the immune pathogenesis of IRIS still needs to be determined, reactivation of latent infections, including herpes viruses, has already been described [32]. The administration of PEG-IFN-α 2a in our patient with chronic active hepatitis B infection may have altered the immune response and may have elevated the amount of plasma cytokines inducing an IRIS condition that led to reactivation of underlying HHV-6 and/or HHV-7 infection and the development of typical PR.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenetic mechanisms that trigger the HHV-6 and HHV-7 reactivation in PR are still poorly understood [31]. Although the immune pathogenesis of IRIS still needs to be determined, reactivation of latent infections, including herpes viruses, has already been described [32]. The administration of PEG-IFN-α 2a in our patient with chronic active hepatitis B infection may have altered the immune response and may have elevated the amount of plasma cytokines inducing an IRIS condition that led to reactivation of underlying HHV-6 and/or HHV-7 infection and the development of typical PR.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of these complications increases with declining CD4 count. HSV-2-seropositive persons with CD4 counts of Ͻ250 cells/ml have an increased risk of GUD and HSV-2 shedding in the first 6 months after starting antiretroviral therapy (ART), but the risk returns to baseline after this period (120). Suppressive anti-HSV therapy reduces the risk of both HSV-2 shedding and GUD after initiation of ART (120).…”
Section: Hsv-2 Infection In Hiv-infected Individualsmentioning
confidence: 99%
“…HSV-2-seropositive persons with CD4 counts of Ͻ250 cells/ml have an increased risk of GUD and HSV-2 shedding in the first 6 months after starting antiretroviral therapy (ART), but the risk returns to baseline after this period (120). Suppressive anti-HSV therapy reduces the risk of both HSV-2 shedding and GUD after initiation of ART (120). Other studies have shown that there is decreased risk of GUD associated with ART, but the overall HSV shedding rate is not significantly different between persons on and off ART (121).…”
Section: Hsv-2 Infection In Hiv-infected Individualsmentioning
confidence: 99%
“…Some studies have shown that suppressive antiretroviral therapy in HIV-positive patients can significantly increase genital ulcer disease (GUD) because of HSV-2 reactivation [125], although some have not observed this phenomenon [126]. Nevertheless, patients receiving cART therapy together with the antiviral acyclovir generally display significantly less GUD and HSV-2 shedding than those receiving cART alone, and thus, HIV + /HSV + individuals are frequently prescribed with acyclovir [125,[127][128][129]. However, the chronic use of acyclovir in these patients has been shown to promote the emergence of HSV isolates that are resistant to this drug.…”
Section: Relationship Between Hsv-2 and Hivmentioning
confidence: 99%